2018
DOI: 10.1111/cen3.12463
|View full text |Cite
|
Sign up to set email alerts
|

Retinoic acid‐inducible gene‐I, melanoma differentiation‐associated gene 5 and C‐X‐C motif chemokine ligand 10 are induced by a Toll‐like receptor 3 agonist in human brain microvascular endothelial cells

Abstract: Objective Brain microvascular endothelial cells (BMEC) are the major component of the blood-brain barrier, and play a critical role in protecting the brain from pathogens. Although Toll-like receptor 3 (TLR3) is known as an important pattern-recognition receptor against viral double-stranded RNA, the downstream reactions of TLR3 in human BMEC are not fully characterized. The purpose of the present study was to investigate the role of TLR3 signaling in the expression of retinoic acid-inducible gene-I (RIG-I), m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 24 publications
1
3
1
Order By: Relevance
“…However, the regulatory mechanisms of CXCL10 production in RFLS have not been fully characterized. The TLR3/IFN-β/MDA5/CXCL10 axis demonstrated by our study corroborates previous findings of the role of MDA5 in regulating CXCL10 expression in glomerular mesangial cells [ 15 ], brain microvascular endothelial cells [ 26 ], and hepatocellular carcinoma cells [ 27 ]. The present study revealed a new role of MDA5 in RA synoviocytes and offers new insights about RA sterile inflammation mechanisms.…”
Section: Discussionsupporting
confidence: 91%
“…However, the regulatory mechanisms of CXCL10 production in RFLS have not been fully characterized. The TLR3/IFN-β/MDA5/CXCL10 axis demonstrated by our study corroborates previous findings of the role of MDA5 in regulating CXCL10 expression in glomerular mesangial cells [ 15 ], brain microvascular endothelial cells [ 26 ], and hepatocellular carcinoma cells [ 27 ]. The present study revealed a new role of MDA5 in RA synoviocytes and offers new insights about RA sterile inflammation mechanisms.…”
Section: Discussionsupporting
confidence: 91%
“…ZAPS, but not ZAPL, enhances RIG-I-mediated signaling in HEK293 cells after viral infection [7]. We have previously reported that RIG-I is involved in CXCL10 expression induced by TLR3 signaling in hCMEC/D3 cells [19]. However, ZAP knockdown did not affect poly ICinduced expression of RIG-I and CXCL10 in hCMEC/D3 cells in the present study.…”
Section: Discussion/conclusioncontrasting
confidence: 74%
“…We have previously reported that cultured hCMEC/D3 cells express TLR3 [18]. Adding poly IC to culture medium induces the expression of IFN-β, a type I IFN, via activation of IRF3 and NF-κB, and newly synthesized IFN-β is involved in RIG-I and CXCL10 expression in hCMEC/D3 cells [19]. The aim of this study was to investigate ZAP expression in cultured hCMEC/D3 cells treated with poly IC.…”
Section: Introductionmentioning
confidence: 99%
“…IFN-b is a key cytokine in innate immune reactions in the downstream of TLR3. 19 We have previously reported that the treatment of hCMEC/D3 cells with poly IC induces the expression of CCL5 in an IFN-b-independent manner, 15 whereas CXCL10 20 and ISG60 17 are induced by poly IC in an IFN-b-dependent manner. Thus, poly IC induces the expression of various genes either in an IFN-bindependent or -dependent manner.…”
Section: Discussionmentioning
confidence: 98%